Increasing hepatitis virus screening uptake at worksites in Japan using nudge theory and full subsidies - Jun Fukuyoshi; Masaaki Korenaga; Yui Yoshii; Lek Hong; Soichiro Kashihara; Byron Sigel; Toru Takebayashi (Komiyama Printing Co. Ltd, 2021)
Abstract Background Despite the importance of hepatitis screening for decreasing liver cancer mortality, screening rates remain low in Japan. Previous studies show that full subsidies increase screening uptake, but full subsidies are costly and difficult to implement in low-resource settings. Alternatively, applying nudge theory to the message design could increase screening at lower costs. This study examined the effects of both methods in increasing hepatitis virus screening rates at worksites. Methods 1496 employees from a Japanese transportation company received client reminders for an optional hepatitis virus screening before their general health checkups. Groups A and B received a client reminder designed based on the principles of "Easy" and "Attractive," while the control group received a client reminder not developed using nudge theory. Additionally, hepatitis virus screening was offered to the control group and group A for a co-payment of JPY 612, but was fully subsidized for group B. The hepatitis virus screening rates among the groups were compared using a Chi-square test with Bonferroni correction, and the risk ratios of group A and group B to the control group were also calculated. To adjust for unobservable heterogeneity per cluster, the regression analysis was performed using generalized linear mixed models. Results The screening rate was 21.2%, 37.1%, and 86.3% for the control group, group A, and group B, respectively. And the risk ratio for group A was 1.75 (95% confidence interval [CI] 1.45-2.12) and that of group B was 4.08 (95% CI 3.44-4.83). The parameters of group A and group B also were significant when estimated using generalized linear mixed models. However, the cost-effectiveness (incremental cost-effectiveness ratio (ICER)) of the nudge-based reminder with the full subsidies was lower than that of only the nudge-based reminder. Conclusions While fully subsidized screening led to the highest hepatitis screening rates, modifying client reminders using nudge theory significantly increased hepatitis screening uptake at lower costs per person.